Those Who Count : Expert Practicies of Roma Classification - Surdu, Mihai (Book collections on Project MUSE., 2016)
"The book scrutinizes the scientific and expert practices of Roma classification in a historic perspective focusing on the expert discourses that gave rise to Roma-related policies in the last two decades. Epistemic communities that classify and describe Roma obey the commandments of political regimes in power, to the disciplinary research traditions and to the organizational interests. The resultant of knowledge subordination is a negative Roma public image that creates and reinforce stereotypical views held by the society at large. Case studies and thorough examples in the book show that both the census as an administrative and scientific practice, as well as policy related surveys are crafting Roma identity in an essentializing manner. The census reifies Roma by the use of mutually exclusive categories and by post-codification of data while the surveys do so by unfounded representativeness claims. Roma are relegated by the experts to several types of determinism: to a social category, to a frozen culture and to a biologized entity. The recently reemerged scholarship in Roma-related genetics imported classifications and narrations created in the fields of social sciences and contributed to circulation of bio-historical narratives that singularize, pathologize and exoticize Roma"--Provided by publisher